Clinical Profile and Surgical Outcomes of Hirschsprung's Disease in Benghazi: A Retro spective Study (2019-2024). - A. Elfrgani, Lobna; A. Ghannay , Sumeia; I. Sati, Ali; N. Alfarsi, Rodaina; A. El-turbi , Ghofran; A. Aloribe, Aya; M. Mahmoud, Eslam; Billah I. Attiatallah , AlMotasem (Libyan Journal of Science &Technology, 2026)
Hirschsprung’s disease (HSD) is a congenital disorder of the enteric nervous system (ENS) due to defective migration of neural crest cells, resulting in a segment of the colon without ganglion cells which leads to functional obstruction of the intestines. The disease affects 1 in 5,000 live births, with males being more commonly affected. Surgical resection is often required for man agement, although 30-50% of patients may experience persistent symptoms. This study aims to evaluate the clinical presentation, diagnostic methods, extent of aganglionosis, and surgical out comes of pediatric Hirschsprung’s disease at Benghazi Children’s Hospital (2019–2024), with particular focus on gender differences and complications such as Hirschsprung-associated en terocolitis. A retrospective study was carried out by reviewing the medical records of 116 pa tients who were diagnosed with Hirschsprung disease and came for follow-up to receive the de signed treatment in the Pediatric Surgery Department at Benghazi Children’s Hospital between 2019-2024. Of the 116 patients, 88 were males, and 28 were females, with a predominant age of 1-5 years old. Most of the patients had short-segment disease (75%) and were diagnosed with rectal biopsy (93%). Colostomy was performed as a temporary measure in most of the cases (72%), with reported complications of enterocolitis in 56%. This 5 years study suggests a higher incidence of HSD in Benghazi and the importance of increasing public awareness of the symp toms can promote early medical visits and early diagnosis in the neonatal period which may re duce the complexity of the disease and the need for multiple surgeries